The “2.8 ka BP Cold Event” Indirectly Influenced the Agricultural Exploitation During the Late Zhou Dynasty in the Coastal Areas of the Jianghuai Region - Jia, Xin; Zhao, Dongsheng; Storozum, Michael J.; Shi, Hongwei; Bai, Guozhu; Liu, Zhen; Hu, Zhujun; Sun, Liqiang; Wang, Qi; Li, Haiming (Frontiers in Plant Science, 2022)
As a global cooling event, many of the climatic and socio-cultural mechanisms that resulted in changes after the 2.8 ka BP event remain unclear. In China, this period roughly corresponds with the Zhou Dynasty (1046-212 BC), a critical period when ancient Chinese civilization was experiencing significant cultural and technological changes, including the movement of people to modern-day Jiangsu Province, where they intensively used the natural resources found in this the coastal area. Recent archaeobotanical evidence, and two radiocarbon dates on wheat and foxtail millet, indicate that the Datongpu site, which dates to 2750-2350 cal BP, was occupied during this period of transition around the 2.8 ka BP climate event. In total, our investigations recovered 3399 carbonized seeds from seventy-four flotation samples, of which rice, foxtail millet, broomcorn millet, and wheat seeds where predominant along with 2296 weed seeds. Additionally, we identified several rice spikelets and wheat rachises. The high number of carbonized rice grains indicates that rice farming was the primary crop in an otherwise mixed rice-dry farming system at Datongpu. In addition, we argue that the “2.8 ka BP cold event” probably influenced population growth and caused food shortages throughout Central China, leading people to migrate southeastward along the Huai River to the coastal areas of Jianghuai Region. We argue that this abrupt shift in the climate indirectly facilitated the exploitation and emergence of large-scale agriculture in this area. Our study provides an example for the indirect impact of climate change in areas with relatively favorable climate conditions.